Cytosolic HSC70s repress heat stress tolerance and enhance seed germination under salt stress conditions. (22nd March 2021) - Zhao, Huimei; Jan, Asad; Ohama, Naohiko; Kidokoro, Satoshi; Soma, Fumiyuki; Koizumi, Shinya; Mogami, Junro; Todaka, Daisuke; Mizoi, Junya; Shinozaki, Kazuo; Yamaguchi‐Shinozaki, Kazuko
Abstract: Heat shock factor A1 (HsfA1) family proteins are the master regulators of the heat stress‐responsive transcriptional cascade in Arabidopsis. Although 70 kDa heat shock proteins (HSP70s) are known to participate in repressing HsfA1 activity, the mechanisms by which they regulate HsfA1 activity have not been clarified. Here, we report the physiological functions of three cytosolic HSP70s, HSC70‐1, HSC70‐2 and HSC70‐3, under normal and stress conditions. Expression of the HSC70 genes was observed in whole seedlings, and the HSC70 proteins were observed in the cytoplasm and nucleus under normal and stress conditions, as were the HsfA1s. hsc70‐1/2 double and hsc70‐1/2/3 triple mutants showed higher thermotolerance than the wild‐type (WT) plants. Transcriptomic analysis revealed the upregulation of heat stress‐responsive HsfA1‐downstream genes in hsc70‐1/2/3 mutants under normal growth conditions, demonstrating that these HSC70s redundantly function as repressors of HsfA1 activity. Furthermore, hsc70‐1/2/3 plants showed a more severe growth delay during the germination stage than the WT plants under high‐salt stress conditions, and many seed‐specific cluster 2 genes that exhibited suppressed expression during germination were expressed in hsc70‐1/2/3 plants, suggesting that these HSC70s also function in the developmental transition from seed to seedling under high‐salt conditions by suppressing the expression of cluster 2 genes. Abstract : Three cytosolic HSP70s, HSC70‐1, HSC70‐2 and HSC70‐3, redundantly function as repressors of HsfA1 family proteins that are the master regulators of the heat stress‐responsive transcriptional cascade in Arabidopsis. Furthermore, these HSC70s also function in the developmental transition from seed to seedling under high‐salt conditions by suppressing the expression of the many seed‐specific genes.